Hadith #212 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Ibn ‘Umar reported that the Prophet, may Allah bless him and grant him peace, “All of you are shepherds and each of you is responsible for his flock. A man is the shepherd of the people of his house and he is responsible. A woman is the shepherd of the house of her husband and she is responsible. Each of you is a shepherd and each is responsible for his flock.”
Grade:

Hadith #213 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Grade:

Hadith #214 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Ibn ‘Umar reported that he heard the Messenger of Allah, may Allah bless him and grant him peace, say, “All of you are shepherds and each of you is responsible for his flock. A woman is the shepherd of the house of her husband and she is responsible as is the servant in regard to his master’s property.”
Grade:

Hadith #215 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Jabir ibn ‘Abdullah al-Ansari reported that the Prophet, may Allah bless him and grant him peace, said, “Whoever has a favour done for him should repay it. If he cannot find anything he can use to repay it, he should praise the one who did it. When he praises him, he thanks him. If he is silent, he is ungrateful to him. If someone adorns himself with something he has not been given, it is as if he was wearing a false garment.”
Grade:

Hadith #216 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Ibn ‘Umar reported that the Messenger of Allah, may Allah bless him and grant him peace, said, “Anyone who seeks refuge in Allah will find refuge with Him. Anyone who asks from Allah will be receive. Anyone who does a favour should repay it. If you do not find anything, then make supplication for the doer of the favour so that he knows that you have repaid him.”
Grade:

Hadith #217 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Anas reported that the Muhajirun said, “Messenger of Allah, the Ansar have taken all the reward!” He said, “No, not as long as you make supplication for them and praise them for it.”
Grade:

Hadith #218 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Abu Hurayra reported that the Prophet, may Allah bless him and grant him peace, said, “He who does not thank people does not thank Allah.”
Grade:

Hadith #219 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Abu Hurayra reported that the Prophet, may Allah bless him and grant him peace, said, “Allah ta’ala said to the self, ‘Go forth.’ It replied, ‘I only go forth reluctantly.'”
Grade:

Hadith #220 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Abu Dharr reported that the Prophet, may Allah bless him and grant him peace, was asked, “What action is best?” He replied, “Belief in Allah and jihad in His way.” He was asked, “Which slaves are best?” He replied, “The highest in price and most precious to their people.” He said, “What do you think I should do if I am unable to fight?” He replied, “Help someone in trouble or work for someone who does not work.” He asked, “What do you think that I should do if I am too
Grade: